Neuronal and glial markers are differently associated with computed tomography findings and outcome in patients with severe traumatic brain injury: a case control study - Mondello, Stefania; Papa, Linda; Buki, Andras; Bullock, M Ross; Czeiter, Endre; Tortella, Frank C; Wang, Kevin K; Hayes, Ronald L (Critical care (London, England), 2011)
Authors of several studies have studied biomarkers and computed tomography (CT) findings in the acute phase after severe traumatic brain injury (TBI). However, the correlation between structural damage as assessed by neuroimaging and biomarkers has not been elucidated. The aim of this study was to investigate the relationships among neuronal (Ubiquitin carboxy-terminal hydrolase L1 [UCH-L1]) and glial (glial fibrillary acidic protein [GFAP]) biomarker levels in serum, neuroradiological findings and outcomes after severe TBI. The study recruited patients from four neurotrauma centers. Serum samples for UCH-L1 and GFAP were obtained at the time of hospital admission and every 6 hours thereafter. CT scans of the brain were obtained within 24hrs of injury. Outcome was assessed by Glasgow Outcome Scale (GOS) at discharge and at 6 months. 81 severe TBI patients and 167 controls were enrolled. The mean serum levels of UCH-L1 and GFAP were higher (p < 0.001) in TBI patients compared to controls. UCH-L1 and GFAP serum levels correlated significantly with Glasgow Coma Scale (GCS) and CT findings. GFAP levels were higher in patients with mass lesions than in those with diffuse injury (2.95 ± 0.48 ng/ml versus 0.74 ± 0.11 ng/ml) while UCH-L1 levels were higher in patients with diffuse injury (1.55 ± 0.18 ng/ml versus 1.21 ± 0.15 ng/ml, p = 0.0031 and 0.0103, respectively). A multivariate logistic regression showed that UCH-L1 was the only independent predictor of death at discharge [adjusted odds ratios 2.95; 95% confidence interval, 1.46-5.97], but both UCH-L1 and GFAP levels strongly predicted death 6 months post-injury. Relationships between structural changes detected by neuroimaging and biomarkers indicate each biomarker may reflect a different injury pathway. These results suggest that protein biomarkers could provide better characterization of subjects at risk for specific types of cellular damage than that obtained with neuroimaging alone, as well as provide valuable information about injury severity and outcome after severe TBI.